Comparison of efficacy, safety, patients' quality of life, and doctors' occupational stress between lenalidomide‐based and bortezomib‐based induction in patients with newly diagnosed multiple myeloma. (2nd February 2021) - Xu, Limei; Liu, Junru; Huang, Beihui; Kuang, Lifen; Gu, Jingli; Chen, Meilan; Zou, Waiyi; Li, Juan
Abstract: Background: In the new therapeutic era, comparisons between regimens containing lenalidomide and bortezomib are needed. Methods: In this single‐center, prospective study, patients received four to six cycles of lenalidomide+liposomal doxorubicin+dexamethasone (RAD) or bortezomib+liposomal doxorubicin+dexamethasone (PAD) every 4 weeks, with subsequent autologous stem cell transplantation (ASCT) and maintenance therapy. We compared the efficacy, safety, patients' quality of life, and doctors' occupational stress between RAD and PAD induction in newly diagnosed MM patients. Results: The complete response (CR) rate was comparable between the RAD and PAD groups after induction (30.8% vs. 32.0%, p = 0.92). Common adverse events, including infections, peripheral neuropathy, and gastrointestinal disturbances, were more frequent in the PAD group, while leukopenia and rashes were more common in the RAD group. Compared with PAD, RAD improved patients' quality of life more quickly and caused less occupational stress for doctors. However, only 31.6% of patients collected adequate CD34+ cells (≥2 × 10 6 /kg) in the RAD group, which was significantly lower than that in the PAD group (95.5%, p < 0.001). The number of CD34+ cells collected was significantly higher in patients within three courses of RAD than in patients with four or five to six courses (14.18 ± 13.57 vs. 2.07 ± 2.42 vs. 1.51 ± 1.81 × 10 6 /kg, p = 0.028). The median progression‐free survival and overall survival of the two groups were not reached by the end of follow‐up. Conclusion: Compared to PAD, RAD induction had comparable efficacy and a significantly better safety profile, improved quality of life for patients, and reduced occupational stress for doctors. However, RAD induction may need to be limited to four cycles to avoid irreversible damage to hematopoietic stem cells. Clinical trial registration: This study was registered at www.chictr.org.cn (ChiCTR1900021558). Abstract : Compared to PAD, RAD induction had a comparable efficacy and significantly better safety profile, improved quality of life for patients and reduced occupational stress for doctors. However, RAD had an effect on stem cell collection, which may need to be limited to 4 cycles to avoid irreversible damage to hematopoietic stem cells.